Strategies, Tactics, and Forms of Interaction between Rural Communities and Governmental Bodies during the Administrative and Territorial Reform of 1962–1966: "Letters to the Authorities" from the Altai Region - Alexey V. Rykov (СибСкрипт)
Well-organized relations between the authorities and the population provide prompt feedback on the effectiveness of state reforms. The so-called letters to the authorities were a means of obtaining feedback from the population in the USSR. The author analyzed the archival letters to the authorities sent by the rural population of the Altai Region during the administrative and territorial reform of 1962–1966. The research objective was to reveal the strategies, tactics, and forms of interaction between the rural population and the authorities. The materials from the State Archive of the Altai Region included letters to the authorities and legal documents received by the regional executive committee, which were directly related to the reform in question. The rural population turned to two main strategies to solve the problems caused by the new administrative and territorial division: 1) they tried to achieve a complete restoration of the liquidated district; 2) they attempted to transfer their village to the subordination of the neighboring district. The senders adhered to passive or active tactics but failed in all their attempts to restore their districts. The strategy of transferring villages, village councils, collective farms, or state farms to the subordination of an adjacent district or region proved to be more successful in terms of logistics and management. To resolve the transfer issues, the regional authorities used an established decision-making pattern, in which they were not limited by the necessity to merge the districts, imposed by the central authorities.